Novel discovery of Extended Spectrum β-lactamase (ESBL) Pluralibacter gergoviae in acute urinary tract infection and urolithiasis. (28th October 2021) - Coate, E; Merchen, T; Cybulski, R; Collier, R; Mc Gann, P; Mills, E
Abstract: Introduction/Objective: This case study describes the diagnosis, treatment, whole genome sequencing (WGS) and antibiotic resistance characterization from the ESBL-producing Pluralibacter gergoviae, a multi-drug resistant organism (MDRO) with a previously-documented presence in foodstuffs and cosmetics. Methods/Case Report: A 39-year-old Hispanic American woman was admitted to the emergency department (ED) for fever, suprapubic tenderness, and pyuria. Three days prior to admission, patient underwent elective bilateral lithotripsy for retained nephrolithiasis. Seven days prior to ED admission, patient had an "Orgasm Shot" (O-Shot) which consists of platelet rich plasma that is drawn from the patient and injected into her vulvar area and around her clitoris to increase stimulation potential during orgasm. The patient was started on broad spectrum antibiotics, receiving Vancomycin and Ceftriaxone 1 gram 1 gram IV every 12 hours, intravenously. Urine cultures yielded two organisms, including a lactose fermenting as well as a non-lactose fermenting Gram negative rod. Mass spectrometry-based identification was successful in identifying the non-lactose fermenting colony as Pseudomonas aeruginosa, which also identified from a blood culture collected from the patient upon presentation to the ED. The lactose fermenting colony resulted in no identification by mass spectrometry but was identified using biochemical methods as Pluralibacter gergoviae, a recently-reclassified taxonomy previously identified as Enterobacter gergoviae. The P. gergoviae isolate was submitted to the Multidrug-Resistant Organism Repository (MRSN) at Walter Reed Army Institute of Research (WARIR) for WGS on Illumina Miseq. Sequencing and phenotypic/ genotypic data on isolate confirmed this as an ESBL P. gergoviae organism. Results (if a Case Study enter NA): NA Conclusion: Summary data on possible epidemiological associations, antibiotic susceptibility testing, antibiotic resistance genes identified, and information on the antibiotic resistance plasmids will be presented. These findings from the WGS data, antibiotic susceptibilities will provide a lessons-learned for other clinical microbiology labs on how to identify unusual organisms such as P. gergoviae.